Nanofiber-mediated microRNA delivery to enhance differentiation and maturation of oligodendroglial precursor cells - Diao, Hua Jia (2016)
Remyelination in the central nervous system (CNS) is critical in the treatment of many neural pathological conditions. Unfortunately, the ability to direct and enhance oligodendrocyte (OL) differentiation and maturation remains limited. It is known that microenvironmental signals, such as substrate topography and biochemical signaling, regulate cell fate commitment. Therefore, in this study, we developed a nanofiber-mediated microRNA (miR) delivery method to control oligodendroglial precursor cell (OPC) differentiation through a combination of fiber topography and gene silencing. Using poly(ε-caprolactone) nanofibers, efficient knockdown of OL differentiation inhibitory regulators were achieved by either nanofiber alone (20-40%, p<0.05) or the synergistic integration with miR-219 and miR-338 (up to 60%, p<0.05). As compared to two-dimensional culture, nanofiber topography enhanced OPC differentiation by inducing 2-fold increase in RIP(+) cells (p<0.01) while the presence of miRs further enhanced the result to 3-fold (p<0.001). In addition, nanofiber-mediated delivery of miR-219 and miR-338 promoted OL maturation by increasing the number of MBP(+) cells significantly (p<0.01). Taken together, the results demonstrate the efficacy of nanofibers in providing topographical cues and microRNA reverse transfection to direct OPC differentiation. Such scaffolds may find useful applications in directing oligodendrocyte differentiation and myelination for treatment of CNS pathological conditions that require remyelination.